Symbiotic diazotrophs in response to yak grazing and Tibetan sheep grazing in Qinghai-Tibetan plateau grassland soils - Sun, Shengnan; Zhao, Yi; Dong, Quanmin; Yang, Xiaoxia; Liu, Yuzhen; Liu, Wentao; Shi, Guang; Liu, Wenting; Zhang, Chunping; Yu, Yang (Frontiers in Microbiology, 2023)
Grazing by local livestock is the traditional human practice in Qinghai-Tibetan Plateau grassland, and moderate intensity grazing can maintain high productivity and diversity of alpine grassland. Grazing ecosystems are often nitrogen-limited, but N 2 -fixing communities in response to yak grazing and Tibetan sheep grazing in Qinghai-Tibetan Plateau grassland have remained underexplored. In this study, we applied quantitative PCR quantitation and MiSeq sequencing of nifH under yak grazing and Tibetan grazing through a manipulated grazing experiment on an alpine grassland. The results showed that the grazing treatments significantly increased the soil ammonium nitrogen (AN) and total phosphorus (TP), but reduced the diazotrophs abundance.Compared with no grazing treatment, the composition of diazotrophs could be maximally maintained when the ratio of yak and Tibetan sheep were 1:2. The foraging strategies of grazing livestock reduced the legumes biomass, and thus reduced the diazotrophs abundance. Data analysis suggested that the direct key factors in regulating diazotrophs are AN and TP, and the changes of these two soil chemical properties were affected by the dung and urine of herbivore assemblages. Overall, these results indicated that the mixed grazing with a ratio of yak to Tibetan sheep as 1:2 can stabilize the soil diazotrophsic community, suggesting that MG12 are more reasonable grazing regimes in this region.